Hepatitis B virus produced by transfected Hep G2 cells causes hepatitis in chimpanzees. - Acs, G (1987)
We have reported that clonal cells derived from Hep G2 cells transfected with a plasmid containing hepatitis B virus (HBV) DNA secrete spherical and filamentous forms of hepatitis B surface antigen (HBsAg), core particles, and virions into the culture medium. Here we describe the development of typical hepatitis in two chimpanzees following intravenous inoculation with the medium in which the transfected cells had grown. The liver biopsies from these animals showed characteristic lesions in parenchyma and portal tracts, more conspicuous at an earlier time in the chimpanzee that had received a greater number of virions. The amount of HBsAg in the serum of one infected chimpanzee increased with time after the initial inoculation and then decreased concomitantly with the appearance of antibodies against HBsAg and core antigens. HBsAg remained detectable in the other animal throughout the course of the experiment. The levels of hepatitis B "e" antigen in both animals peaked at week 5, signifying the acute phase of the infection. The activities of serum enzymes that are markers for necroinflammation also increased. The hepatitis HBsAg subtype of the virions isolated from the patient whose DNA was cloned and then used for transfection of the Hep G2 cells was the same as that found in the chimpanzees. Furthermore, the restriction enzyme analysis of the viral DNA isolated from the chimpanzees was identical to the cloned DNA. Thus, HBV DNA-transfected Hep G2 cells can support the replication of virions that, in turn, produce hepatitis in chimpanzees.